2022
DOI: 10.3390/ijerph19137997
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rationalization and Upgrading of Industrial Structure on Carbon Emissions in the Beijing-Tianjin-Hebei Urban Agglomeration

Abstract: Carbon dioxide mainly comes from industrial economic activities. Industrial structure optimization is an effective way to reduce carbon dioxide emissions. This paper uses the panel data of 13 cities in the Beijing-Tianjin-Hebei urban agglomeration from 2006 to 2019, uses the Theil index to calculate the industrial structure rationalization index, and uses the proportion of industrial added value to calculate the industrial structure upgrade index. By constructing the STIRPAT model, this paper quantitatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…It is the organic unity of industrial structure rationalization and industrial structure optimization. Therefore, this study analyzed the impact of industrial structure on carbon emission intensity from the perspectives of rationalization and optimization [ 11 ]. In terms of the impact of industrial structure rationalization on carbon emission intensity, as resources flow from sectors with lower productivity to sectors with higher productivity, low-end enterprises with extensive production methods and serious ecological damage in the industrial structure are eliminated, and they gradually evolve to eco-friendly, high-tech industrial sectors [ 16 , 27 ].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the organic unity of industrial structure rationalization and industrial structure optimization. Therefore, this study analyzed the impact of industrial structure on carbon emission intensity from the perspectives of rationalization and optimization [ 11 ]. In terms of the impact of industrial structure rationalization on carbon emission intensity, as resources flow from sectors with lower productivity to sectors with higher productivity, low-end enterprises with extensive production methods and serious ecological damage in the industrial structure are eliminated, and they gradually evolve to eco-friendly, high-tech industrial sectors [ 16 , 27 ].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Since the reform and opening up, China’s economic development has relied on an energy structure dominated by coal, and the industrial structure has become more industrialized, with high carbon emissions [ 10 , 11 ]. According to some scholars, the contribution rate of China’s industrial restructuring to the achievement of carbon intensity goals is more than 70% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technological innovation is the strategic engine for upgrading the industrial structure, improving the technical efficiency of factors, and promoting industrial transformation and upgrading. By studying the Beijing-Tianjin-Hebei urban agglomeration, Runde Gu et al [ 27 ] found that government expenditure on science and technology can promote the upgrading of industrial structure to a certain extent, thereby reducing carbon emissions. Therefore, we propose that:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…From the perspective of “improving quality”, industrial-structure upgrading also plays a positive role in promoting GTFP. Gu et al (2022) argued that industrial-structure upgrading has the effect of curbing pollutant emissions and significantly improves environmental quality [ 47 ]. In addition, the “structural dividend” released by industrial-structure upgrading can promote the emergence of clean industries and provide effective support to improve GTFP.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%